2013
DOI: 10.1001/jamadermatol.2013.2248
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Dermoscopic Characteristics of Desmoplastic Melanomas

Abstract: Though DM can be difficult to diagnose based on clinical morphologic characteristics alone, dermoscopy has proved to be a useful aid during the evaluation of clinically equivocal lesions or those lesions with a benign appearance. The most common dermoscopic clues observed in DMs included atypical vascular structures, peppering, and occasionally other melanoma-specific structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 18 publications
5
35
0
3
Order By: Relevance
“…Both our study and the Jaimes et al 5 study found a high prevalence of atypical vascular structures in DM. This seemed to be one of the main differences when compared to general non-specified melanoma populations 14,15 , which had much lower frequencies of vascular structures.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Both our study and the Jaimes et al 5 study found a high prevalence of atypical vascular structures in DM. This seemed to be one of the main differences when compared to general non-specified melanoma populations 14,15 , which had much lower frequencies of vascular structures.…”
Section: Discussionsupporting
confidence: 78%
“…This seemed to be one of the main differences when compared to general non-specified melanoma populations 14,15 , which had much lower frequencies of vascular structures. However, this difference could be related to Breslow thickness differences, as this dermoscopic feature became more frequent in the general melanoma population with increasing Breslow thickness (up to 47% for Breslow thickness >0.75mm 14 ), and our study had a mean Breslow thickness of 3.3mm (standard deviation 2.36mm) in the DM population and the Jaimes et al 5 study had a mean Breslow thickness of 3.38mm in their DM population (range 0.5–12.0mm).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Multiple colors (at least 4) are often considered a dermoscopic criterion of melanoma, also in the desmoplastic type. 24,25 Reflectance confocal microscopy…”
Section: 11mentioning
confidence: 99%